Experimenting with Unconditional Basic Income Lessons from the Finnish BI Experiment 2017-2018 - Kangas, Olli; Jauhiainen, Signe; Simanainen, Miska; Ylikännö, Minna (Edward Elgar Publishing, 2021)
This discerning book provides a comprehensive analysis of the nationwide randomised Finnish basic income experiment 2017 to 2018, from planning and implementation through to the end results. It presents the background of the social policy system in which the experiment was implemented and details the narratives of the planning process alongside its constraints, as well as a final evaluation of the results.